Pengaruh Perceıve Informatıon, Trust, Socıal Medıa Marketıng Dan Brand Image Terhadap Nıat Belı Konsumen Pada Brand Mınuman Boba Dı Kota Batam - Lady Lady; Jewell Jewell (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
Nowadays, the rapid development of the internet has greatly affected many people’s life especially towards the franchise industry in Indonesia. Food and beverage industry is one of the industry which has an intense business competition, especially in this case is boba drink. The purpose of this study is to test a framework for the significant effect between Perceive Information, Trust, Social Media Marketing, and Brand Image towards behavioral intention with trust and brand image as the intervening variables in Boba Drink in Batam city. The respondents in this study are the customer who has previously purchased one of the Boba Drink in Batam city. The sample's criterion used in this study is non-probability with the judgemental sampling method. A total of 292 questionnaires were returned and the data were analyzed using PLS SEM (Structural Equation Modeling). The findings reported in this research demonstrate that Perceive Information, Trust, Social Media Marketing, and Brand Image have a significant effect on behavioral intention with trust dan brand image as the intervening variables.